EFEKTIVITAS METODE IMLĀ’ DALAM MENINGKATKAN PEMBELAJARAN MAHĀRAH KITĀBAH SISWA - Sitorus, Nurul Hafizhah Salsabila; Putri, Tarisha; Nurhasanah, Silvy; Nasution, Sahkholid (Jurnal Al-Fatih, 2024)
This paper aims to provide an overview of the effectiveness of the imla method in improving students' learning of marhalah kitabah. The problem that students often face is the difficulty in writing Arabic according to the applicable rules. This research was carried out using the literature study method, examining various sources of primary literature, such as theses, books, journal articles, websites, and other supporting documents. The results of the study show that the imla method can be an effective solution in overcoming students' difficulties in writing Arabic. This method not only improves students' writing skills technically, but also enriches vocabulary, trains concentration, and provides opportunities for students to self-evaluate through correction of errors found in writing exercises. Overall, the application of the imla method has proven to be effective in improving students' maharah kitabah skills and improving their understanding of Arabic.